Post stress reliability in submicron MOSFET devices - Chen, Tupei. (2008)
In this project, we have conducted a systematic investigation of post-breakdown conduction and its instability in ultrathin SiO2 films as well as various studies of interface degradation, charge trapping and oxide barrier height change in deep submicron MOS devices with ultrathin gate oxide caused by electrical stress.